Perancangan Desain Board Game Pengenalan Budaya Wayang Punakawan Yogyakarta Untuk Anak - Prasetyo, Martinus Eko; Roderico, Brandon (Program Studi Desain Komunikasi Visual. Fakultas Arsitektur dan Desain Jalan Raya Rungkut Madya, Gn.Anyar, Surabaya, Jawa Timur 60294, 2024)
The dominance of western arts and culture in the country makes children think that traditional arts and culture are not trendy and seem old-fashioned nowadays. The impact is felt for the younger generation who don't want to learn, they don't even know Indonesian art and culture. The design of this thesis work is made to produce play media works that are suitable, desirable, and have good benefits for children's growth through board games with the aim of introducing Yogyakarta Punakawan wayang culture to children aged 7-11 years. The research method used is descriptive qualitative and uses interviews with informants, distributing questionnaires to get views from the public, collecting data from the literature, and making observations. The result of this design is a visually appealing board game design, as well as a play style suitable for children aged 7-11 years. By using an illustration style, and choosing the right color to add value to the interest in this board game to be played by children aged 7-11 years.